Classroom Management to Overcome Physical Violence Based On Joyful Learning - Leni Eka Yuniar; Lilis Suwandari (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2026)
Physical violence in primary school environments poses a serious threat to students' psychological safety and learning outcomes. Joyful Learning-based classroom management presents a preventive approach that integrates interactive learning with behavioural regulation strategies. This research employed a descriptive qualitative approach conducted at SDN 2 Mekarsari. Data collection involved classroom observations, in-depth interviews with teachers and the principal, and documentation of learning activities. Thematic analysis was used to examine planning, organising, implementation, evaluation, and supporting or inhibiting factors. Classroom management planning was structured through student profiling, holistic goal setting, classroom layout, and the selection of engaging and interactive learning methods. Organisation included role division among teachers and students, structured scheduling, and the use of positive reinforcement. Implementation showed active teacher involvement as facilitators and supervisors. Evaluation revealed a reduction in physical violence incidents, with improvements in students’ social skills, emotional regulation, and empathy. Key supporting factors included teacher competence, adequate facilities, and parent collaboration. Barriers involved limited resources and student behavioural diversity. The application of Joyful Learning-based classroom management at SDN 2 Mekarsari proved effective in fostering a safe and engaging learning environment. This strategy is promising for broader implementation, supported by policy reinforcement, teacher training, and improved school infrastructure.